Sistem Informasi Pendataan Penduduk Di Desa Sokawera Berbasis Mobile Android dengan MetodeExtreme Programming - Kurniawan, Adrian; Prasetyo, Yogo Dwi; Aldo, Dasril (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Population data collection is an activity of recording population data carried out by data collection officers under the supervision of the village head. The census officer has task of collecting and processing population data. When the data collection officer wanted to process population data, the officer experienced difficulties in finding data. With the development and advancement of information technology, it has a positive impact, namely in social life. This study aims to solve problems with data collection officers, namely searching for and processing population data using an information system designed based on Android. Information system designed with the Extreme Programming method. In this research, there is an information system using the Dart Programming language with the Flutter Framework. The database used is MySQL implemented as RestAPI. Blackbox testing is used to test information systems that aim to determine the function of the information system. The objective of this research is to be able to shorten the time of data collection officers in collecting data and managing population data. The results obtained from this study are the digitalization of population data